Ethics for nurses : theory and practice - Cranmer, Pam (Open University Press, 2013)
Ethics underpin all aspects of nursing activity but the concepts can often seem remote or inaccessible. This refreshing new book will help nurses explore and explain key aspects of ethical nursing practice in a practical and engaging way.